The burden, admission, and outcome of COVID-19 in Africa: protocol for a systematic review and meta-analysis. Issue 1 (1st January 2020) - Tadesse, Degena Bahrey; Gebremeskel, Gebreamlak Gebremedhn; Asefa, Guesh Gebreayezgi; Abay, Mebrahtu; Demoz, Gebre Teklemariam
ABSTRACT: Background : According to the World Health Organization (WHO), the outbreak of coronavirus disease in 2019 (COVID-19) has been declared as pandemic and public health emergency that infected more than 5 million people worldwide at the time of writing this protocol. Strong evidence for the burden, admission, and outcome of COVID-19 has not been published in Africa. Therefore, this protocol will be served as a guideline to conduct a systematic review and meta-analysis of the burden, admission, and outcome of COVID-19 in Africa. Methods : Published and unpublished studies on the burden, admission, and outcome of COVID-19 in Africa and written in any language will be included. Databases (PubMed / MEDLINE, Google Scholar, Google, EMBASE, Web of Science, Microsoft Academic, WHO COVID-19 database, Cochran Library, Africa Wide Knowledge, and Africa Index Medicus) from December 2019 to May 2020 will be searched. Two independent reviewers will select, screen, extract data, and assess the risk of bias. The proportion will be measured using a random-effects model. Subgroup analysis will be conducted to manage hetrogeinity. The presence of publication bias will be assessed using Egger's test and visual inspection of the funnel plots. This systematic and meta-analysis review protocol will be reported per the PRISMA-P guidelines. Conclusion : This systematic review and meta-analysis protocol will be expected to quantify the burden, admission, and outcome of COVID-19 in Africa. Systematic review registration : This protocol was submitted for registration with the International Prospective Register of Systematic Reviews (PROSPERO) in March 2020 and accepted with the registration number: CRD42020179321(https://www.crd.york.ac.uk/PROSPERO ).